Amorphous alloy elastomer and torque sensor
By using amorphous alloy elastomer, combined with vacuum arc smelting and rapid cooling forming technology, an amorphous alloy elastomer with high yield strength, low Young's modulus and high sensitivity is prepared, solving the problem of difficult harmony between stiffness and sensitivity of torque sensors, and achieving high precision and high reliability torque measurement.
Patent Information
- Application Number
- CN202411699892.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-03-21
AI Technical Summary
Existing torque sensors have limitations in material selection, structural design and performance optimization, making it difficult to take into account high strength and low modulus characteristics, resulting in difficult to harmonize stiffness and sensitivity.
Amorphous alloy elastomer is used, and the chemical formula is ZraTibFecNbdMe, where M is an element in Cr, Al, B or S. Through vacuum arc smelting and rapid cooling forming, an amorphous alloy elastomer with high yield strength, low Young's modulus and high sensitivity is prepared, and a torque sensor structure with simple structure, low manufacturing cost, stable and reliable performance is designed.
The high strength, low modulus and high sensitivity of torque sensors are achieved, solving the problem of difficult reconciliation between rigidity and sensitivity of traditional sensors, and improving measurement accuracy and signal stability.
Smart Images

Figure CN119663141A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of torque sensors, and more specifically, to an amorphous alloy elastomer and a torque sensor used in robot joints. Background Art
[0002] The statements in this section are only intended to provide background information related to the present invention to help understand the present invention, and such background information does not necessarily constitute prior art. In the absence of evidence that the relevant information has been disclosed before the application date of the present invention, the relevant information should not be regarded as prior art.
[0003] The core function of a torque sensor, also known as a torque sensor, torque sensor, torque sensor or torque meter, is to accurately sense and detect the torsional torque on rotating or non-rotating mechanical parts. Through the built-in circuit mechanism, the sensor can accurately convert the physical change of torque into an electrical signal.
[0004] In the technical system of robot joints, torque sensors play a vital monitoring role and are integrated into each joint unit of the robot. In the design and manufacture of torque sensors, the performance of the elastomer has always been the key factor in determining the overall performance of the sensor. Traditionally, high-strength alloy steel and low-modulus aluminum alloy, as elastomer materials, have met the basic needs of sensors to a certain extent, but both have limitations in performance. Although high-strength alloy steel has excellent strength, its Young's modulus is high, which limits the sensitivity of the sensor; and although low-modulus aluminum alloy has high sensitivity, its strength is low, making it difficult to meet the requirements of large range and bending moment resistance.
[0005] At present, there are still many challenges in material selection, structural design and performance optimization of torque sensors. In order to comprehensively improve the overall performance and practicality of torque sensors, it is necessary to explore new materials and technical solutions to overcome the limitations of existing technologies. Specifically, it is necessary to develop an amorphous alloy elastomer material that has both high strength and low modulus characteristics and can meet the specific needs of torque sensors; at the same time, it is also necessary to design a torque sensor structure with simple structure, low manufacturing cost, stable and reliable performance to meet market demand and practical application requirements. Summary of the invention
[0006] In view of the above-mentioned deficiencies in the prior art, an object of the present invention is to provide an amorphous alloy elastomer and a torque sensor particularly for use at a robot joint.
[0007] To achieve the above object, the first aspect of the present invention provides an amorphous alloy elastomer, wherein the chemical formula of the amorphous alloy is Zr a Ti b Fe c Nbd M e , wherein M is one element selected from Cr, Al, B or S, and a, b, c, d and e satisfy the following conditions: 40≤a≤55, 12≤b≤27, 6≤c≤20, 3≤d≤20, and 0≤e≤6.
[0008] In some embodiments, the atomic ratio d of Nb satisfies the following condition: 6≤d≤12.
[0009] In some embodiments, when M is chromium (Cr), the value of e is 0<e≤5.
[0010] In some embodiments, when M is aluminum (Al), the value of e is 0<e≤6.
[0011] In some embodiments, when M is boron (B), the value of e is 0<e≤5.
[0012] In some embodiments, when M is sulfur (S), the value of e is 0<e≤3.
[0013] In some embodiments, the Young's modulus of the amorphous alloy elastomer is 90 GPa-114 GPa; and / or the yield strength of the amorphous alloy elastomer is 1700 MPa-2400 MPa; and / or the sensitivity of the amorphous alloy elastomer is 6.18 mV / N m-7.34 mV / N m.
[0014] According to the amorphous alloy elastomer of the first aspect of the present invention,
[0015] The preparation method of the amorphous alloy is as follows: -3 Pa to 6×10^ -3 Under a vacuum condition of 1.50 Pa, the raw materials of the amorphous alloy are melted and rapidly cooled to form. The melting is at least one of vacuum arc melting, induction heating melting or arc melting.
[0016] The preparation method of the amorphous alloy includes a casting method or a die-casting method, and the cooling rate of the amorphous alloy during the preparation process is greater than 10 6 K / s.
[0017] The mold used to prepare the amorphous alloy is a copper mold, and the size of the copper mold matches the size of the amorphous alloy.
[0018] The thickness of the amorphous alloy can be controlled by adjusting the size of the mold. Preferably, the raw material of the amorphous alloy elastomer has a thickness of 4-15 mm, and a length and width of not less than 40 mm.
[0019] The second aspect of the present invention provides a torque sensor particularly for use at robot joints, comprising an amorphous alloy elastomer and a strain gauge, wherein the amorphous alloy elastomer is a circular sheet elastomer, the sheet elastomer comprising a fixed mounting surface, and strain grooves having side walls and a bottom wall are arranged on the upper and lower sides of the fixed mounting surface, and each of the strain grooves is connected through a through groove, and the through groove comprises a first groove extending radially along the sheet elastomer and arranged on both sides of the strain groove, and a second groove extending circumferentially along the sheet elastomer and connecting two adjacent first grooves, the width of the through groove is 0.8-1.0 mm, and the strain gauge is arranged on the bottom wall of the strain groove.
[0020] Furthermore, the sheet-like elastic body includes a loading and mounting surface, the second groove is arranged circumferentially along the loading and mounting surface, and the through groove is arranged for relieving stress and arranging circuits.
[0021] Furthermore, the sheet-like elastic body is in a stepped flange shape, and is provided with the fixed installation surface, the loading installation surface and the centering structure in sequence in the order of increasing thickness.
[0022] According to the second aspect of the present invention, a torque sensor for a robot joint, wherein:
[0023] The strain grooves are evenly distributed along the horizontal direction of the fixed installation surface, the width of the strain grooves is greater than the width of the through grooves, and the widths of the first grooves and the second grooves are the same.
[0024] The fixed installation surface, the loading installation surface and the centering structure are arranged on different horizontal planes with decreasing diameters in sequence.
[0025] The strain gauges are evenly distributed along the horizontal direction of the fixed installation surface.
[0026] A plurality of threaded holes are provided on the fixed installation surface and the loading installation surface. The threaded holes are evenly distributed along the horizontal direction of the centering structure and are staggered with the strain grooves.
[0027] The through groove is processed by milling or water jet processing.
[0028] The torque sensor has a measuring range of 50 to 400 (N∙m).
[0029] The sensitivity of the torque sensor is not less than 3.0% mV / (V*N∙m).
[0030] The repeatability of the torque sensor is 0.01% FS~0.5% FS.
[0031] The linear error of the torque sensor is 0.01% FS~1% FS.
[0032] The hysteresis of the torque sensor is 0.01% FS~0.5% FS.
[0033] The zero drift of the torque sensor is 0.01% FS~0.3% FS.
[0034] Compared with the prior art, the amorphous alloy elastomer and the torque sensor for robot joints of the present invention may have but are not limited to the following beneficial effects:
[0035] 1. The amorphous alloy elastomer of the present invention has excellent mechanical properties, such as high strength, high hardness, high toughness and wear resistance, while achieving high yield strength, low Young's modulus and high elastic limit, effectively solving the problem of the difficulty in reconciling stiffness and sensitivity in traditional sensors.
[0036] 2. The amorphous alloy elastomer of the present invention has unique processing properties. The amorphous alloy elastomer prepared by casting and die-casting has small residual stress, high density and excellent surface finish. The present invention not only improves the processing accuracy and product consistency of the amorphous alloy elastomer, but is also suitable for mass production, significantly reducing the preparation cost and production cycle.
[0037] 3. The torque sensor for robot joints of the present invention is made of amorphous alloy elastomer, which is constructed to separate stress through a through groove with a width of 0.8-1.0 mm. The narrow through groove can reduce stress concentration and avoid structural damage caused by excessive local stress. When the torque sensor is subjected to bending moment, the through groove can isolate most of the bending moment, significantly reducing the interference of the bending moment on the torque measurement accuracy of the torque sensor. In addition, the through groove is processed by milling or water jet technology, which effectively avoids the change of material properties caused by high temperature during wire cutting.
[0038] 4. The structure of the amorphous alloy elastomer of the present invention adopts a stepped flange shape, wherein the fixed mounting surface, the loading mounting surface and the centering structure are not on the same horizontal plane, and the fixed mounting surface, the loading mounting surface and the centering structure are sequentially provided in the order of increasing thickness. This structure not only simplifies the assembly process of the torque sensor, but also avoids the influence of the pre-tightening force of the bolts on the measurement accuracy of the torque sensor during the installation process.
[0039] 5. The torque sensor made of amorphous alloy elastomer of the present invention is not only compact in structure and easy to install and maintain, but also can effectively release stress when the robot joint is subjected to bending moment. When subjected to torque loading, the strain groove can produce large and uniform elastic strain, thereby improving the sensitivity of the torque sensor and the stability of the measurement signal, making it more suitable for the mechanical arm of a high-precision and high-reliability articulated robot. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] The drawings described herein are used to provide a further understanding of the present application and constitute a part of the present application. The illustrative embodiments of the present application and their descriptions are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:
[0041] Figure 1 Schematic diagrams of X-ray diffraction of amorphous alloys according to multiple embodiments of the present invention are shown.
[0042] Figure 2 Schematic diagrams of X-ray diffraction of amorphous alloys according to multiple comparative examples of the present invention are shown.
[0043] Figure 3 A perspective view of a torque sensor according to an embodiment of the present invention is shown.
[0044] Figure 4 A front view of a torque sensor according to an embodiment of the present invention is shown.
[0045] Figure 5 A cross-sectional view of a torque sensor according to an embodiment of the present invention is shown.
[0046] Description of reference numerals:
[0047] 1. Sheet elastic body; 2. Fixed mounting surface; 3. Strain groove; 4. Strain gauge; 5. Second groove; 6. Loading mounting surface; 7. Centering structure; 8. Threaded hole; 9. First groove. DETAILED DESCRIPTION
[0048] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention will be further described in detail below through specific embodiments in conjunction with the accompanying drawings. It should be noted that the embodiments provided by the present invention only represent a part of its various possible implementations, rather than exhausting all embodiments. These embodiments are intended to illustrate the basic principles and advantages of the present invention, but do not constitute a limitation on the scope of protection of the present invention.
[0049] Before specifically introducing the embodiments of the present invention, some of the terms used therein are explained as follows:
[0050] "Amorphous alloy": solidified by ultra-rapid cooling. When the alloy solidifies, the atoms do not have time to arrange themselves in order and crystallize. The resulting solid alloy has a long-range disordered structure. The molecules (or atoms, ions) that make up the material do not have regular periodicity in space, and there are no grains or grain boundaries of crystalline alloys.
[0051] To achieve the above object, the first aspect of the present invention provides an amorphous alloy elastomer, the chemical formula of the amorphous alloy is Zr a Tib Fe c Nb d M e , where M is one of Cr, Al, B or S, and a, b, c, d and e meet the following conditions: 40≤a≤55, 12≤b≤27, 6≤c≤20, 3≤d≤20, and 0≤e≤6. Where a, b, c, d and e are the corresponding atomic proportions of each element in the amorphous alloy. The dominant position of zirconium (Zr) in the alloy can ensure the high hardness and corrosion resistance of the amorphous alloy elastomer. The atomic proportion of titanium (Ti) is 12-27, which can ensure that the amorphous alloy has good toughness and fatigue resistance. Iron (Fe) can form an amorphous alloy with excellent magnetic and mechanical properties after alloying with other elements. The addition of niobium (Nb) can further improve the performance of amorphous alloys in harsh working environments, such as high temperature, high pressure or corrosive environment. The addition of element M can further adjust the properties of amorphous alloys to meet different application requirements.
[0052] In some embodiments, the atomic ratio d of Nb satisfies the following condition: 6≤d≤12. In an amorphous alloy, when the atomic ratio d of Nb is between 6 and 12, the strength and toughness of the material can be significantly improved, and the Nb element can form a stable chemical bond with other elements in the amorphous alloy, thereby enhancing the interaction between atoms and improving the overall mechanical properties of the material. Nb can also significantly improve the wear resistance and corrosion resistance of the amorphous alloy, thereby extending the service life of the material.
[0053] In some embodiments, when M is chromium (Cr), the value of e is 0<e≤5. Specifically, the addition of Cr can significantly improve the strength and hardness of the amorphous alloy while maintaining a certain toughness. When the atomic ratio of Cr is in the range of 0<e≤5, the mechanical properties of the amorphous alloy reach an optimal balance, which is neither too brittle nor too soft. If the Cr content is too high, it will not only affect the glass forming ability, making the material more likely to crystallize during cooling, but also easily lead to brittle fracture and reduce toughness.
[0054] In some embodiments, when M is aluminum (Al), the value of e is 0<e≤6. Specifically, Al can significantly affect the microstructure and properties of the amorphous alloy. An appropriate amount of aluminum can improve the strength and hardness of the alloy while maintaining good toughness and ductility. If the Al content is too much, it will not only cause the melt to be too viscous, which is not conducive to uniform cooling during rapid cooling, but also increase the difficulty of preparing amorphous alloy elastomers and may cause inclusions or component segregation.
[0055] In some embodiments, when M is boron (B), the value of e is 0<e≤5. Specifically, B can significantly improve the amorphous forming ability of the alloy. An appropriate amount of boron can effectively promote the alloy to form a stable amorphous structure during rapid cooling, so that it can maintain excellent performance in a wider temperature range. However, excessive B will reduce the hardenability of the alloy and easily crystallize.
[0056] In some embodiments, when M is sulfur (S), the value of e is 0<e≤3. Specifically, the addition of S sulfur can improve the processing properties of amorphous alloys. Within a specific ratio range (0<e≤3), sulfur can effectively reduce the melting point and viscosity of the alloy, thereby improving its fluidity and plasticity. An appropriate amount of S can also refine the grain size of the alloy and improve the uniformity and density of its microstructure. If the S content is too high, the amorphous alloy is prone to hot brittleness and forms sulfide solid solution impurities with Fe, resulting in reduced plasticity and fatigue strength of the amorphous alloy.
[0057] The following uses a number of embodiments and comparative examples to illustrate the effects of amorphous alloys with different compositions and atomic ratios on amorphous alloy elastomers.
[0058] Example 1
[0059] This embodiment illustrates the alloy Zr provided by the present invention. 52 Ti 24 Fe 13 Nb 11 The invention relates to a preparation method of the present invention, wherein the alloy material is composed of the following elements in atomic proportions: Zr 52%, Ti 24%, Fe 13% and Nb 11%.
[0060] Alloy Zr 52 Ti 24 Fe 13 Nb 11 The alloy is prepared by die casting and has good forming ability, high yield strength and low Young's modulus. According to the mass ratio of the alloy elements, the raw materials of the alloy elements are polished to remove the surface oxide layer, ultrasonically cleaned with ethanol, and accurately weighed before being placed in the crucible of the vacuum arc furnace. Furthermore, the vacuum arc furnace cavity is evacuated to a vacuum of not less than 3×10 -3 Pa vacuum degree to ensure an oxygen-free environment in the crucible of the vacuum arc furnace.
[0061] A high-purity inert gas (such as 99.99% argon) is introduced to ignite the arc. The alloy is then fully melted by the arc generated by the electrode rod, and the alloy is turned over more than five times to ensure uniform alloy composition, and two alloy ingots with a mass of 150 g each are obtained.
[0062] The alloy ingot is moved to a copper mold with a diameter of 30 mm. After the alloy ingot is melted by electric arc, the molten metal of the alloy is sucked into the copper mold by a vacuum pump under the pressure difference between the cavity and the copper mold to form a metal rod and then taken out after cooling. The preparation of alloy rods is convenient for uniform heating in the subsequent die casting process.
[0063] Thoroughly inspect and clean the die-casting mold, and clean its surface with metal polishing paste and alcohol. Place the alloy bar in the quartz tube, install the quartz tube and mold, and pass cooling circulating water into the high vacuum die-casting machine.
[0064] The die casting cavity was evacuated to 6 × 10 - The alloy is melted by induction heating in a vacuum of 3 Pa, and the temperature of the molten metal is continuously monitored using an infrared thermometer. When the temperature of the molten metal reaches 800–830°C, it is immediately injected into the prepared mold. Under the action of water cooling and pressure difference, the molten metal is heated at a speed of more than 10 6 The cooling rate of K / s is fast cooling and forms a dense amorphous alloy plate.
[0065] Finally, turn off the vacuum system and take out the alloy plate after it cools naturally for about 5 minutes.
[0066] like Figure 1 As shown, the cross section of the alloy plate was subjected to X-ray diffraction using a Rigaku X-ray diffractometer equipped with a Cu-Kα radiation source. The obtained X-ray diffraction pattern did not have an obvious diffraction peak, but showed a broad scattering peak, which can be used as an indication of the amorphous state of the alloy elastomer. Table 1 shows the Zr alloy provided by the present invention. 52 Ti 24 Fe 13 Nb 11 The properties and sensitivity of the prepared elastomer materials.
[0067] Example 2
[0068] This embodiment illustrates the alloy Zr provided by the present invention. 49 Ti 22 Fe 16 The preparation method of Nb8Cr5, that is, the alloy material is composed of the following elements in atomic percentage: Zr 49%, Ti 22%, Fe 16%, Nb 8% and Cr 5%. The preparation and characterization steps of the alloy plate in this embodiment refer to Example 1 and are not repeated here. Figure 1 As shown, the alloy Zr provided by the present invention 49 Ti 22 Fe 16 The material properties and sensitivity of the elastomer prepared by Nb8Cr5 are shown in Table 1.
[0069] Example 3
[0070] This embodiment illustrates the alloy Zr provided by the present invention. 50 Ti 23 Fe 14 The preparation method of Nb7Cr6, that is, the alloy material is composed of the following elements in atomic proportions: Zr 50%, Ti 23%, Fe 14%, Nb 7% and Cr 6%. The preparation and characterization steps of the alloy plate in this embodiment refer to Example 1 and are not repeated here. Figure 1 As shown, the alloy Zr provided by the present invention 50 Ti 23 Fe 14 The material properties and sensitivity of the elastomer prepared by Nb7Cr6 are shown in Table 1.
[0071] Example 4
[0072] This embodiment illustrates the alloy Zr provided by the present invention. 53 Ti 20 Fe 15 The preparation method of Nb9Al3, that is, the alloy material is composed of the following elements in atomic proportion: Zr 53%, Ti 20%, Fe 15%, Nb 9% and Al 3%. The preparation and characterization steps of the alloy plate in this embodiment refer to Example 1 and are not repeated here. Figure 1 As shown, the alloy Zr provided by the present invention 53 Ti 20 Fe 15 The material properties and sensitivity of the elastomer prepared by Nb9Al3 are shown in Table 1.
[0073] Example 5
[0074] This embodiment illustrates the alloy Zr provided by the present invention. 44 Ti 23 Fe 18 The preparation method of Nb9Al6, that is, the alloy material is composed of the following elements in atomic proportion: Zr 44%, Ti 23%, Fe 18%, Nb 9% and Al 6%. The preparation and characterization steps of the alloy plate in this embodiment refer to Example 1 and are not repeated here. Figure 1 As shown, the alloy Zr provided by the present invention 44 Ti 23 Fe 18 The material properties and sensitivity of the elastomer prepared by Nb9Al6 are shown in Table 1.
[0075] Example 6
[0076] This embodiment illustrates the alloy Zr provided by the present invention.53 Ti 24 Fe 15 The preparation method of Nb6B2, that is, the alloy material is composed of the following elements in atomic percentage: Zr 53%, Ti 24%, Fe 15%, Nb 6% and B 2%. The preparation and characterization steps of the alloy plate in this embodiment refer to Example 1 and are not repeated here. Figure 1 As shown, the alloy Zr provided by the present invention 53 Ti 24 Fe 15 The material properties and sensitivity of the elastomer prepared by Nb6B2 are shown in Table 1.
[0077] Example 7
[0078] This embodiment illustrates the alloy Zr provided by the present invention. 43 Ti 26 Fe 18 The preparation method of Nb9B4, that is, the alloy material is composed of the following elements in atomic proportions: Zr 43%, Ti 26%, Fe 18%, Nb 9% and B 4%. The preparation and characterization steps of the alloy plate in this embodiment refer to Example 1 and are not repeated here. Figure 1 As shown, the alloy Zr provided by the present invention 43 Ti 26 Fe 18 The material properties and sensitivity of the elastomer prepared by Nb9B4 are shown in Table 1.
[0079] Example 8
[0080] This embodiment illustrates the alloy Zr provided by the present invention. 51 Ti 20 Fe 16 Nb 11 The preparation method of S2, that is, the alloy material is composed of the following elements in atomic percentage: Zr 51%, Ti 20%, Fe 16%, Nb 11% and S 2%. The preparation and characterization steps of the alloy plate in this embodiment refer to Example 1 and are not repeated here. Figure 1 As shown, the alloy Zr provided by the present invention 51 Ti 20 Fe 16 Nb 11 The material properties and sensitivity of the elastomer prepared by S2 are shown in Table 1.
[0081] Example 9
[0082] This embodiment illustrates the alloy Zr provided by the present invention. 49 Ti 24 Fe 15The preparation method of Nb9S3, that is, the alloy material is composed of the following elements in atomic percentage: Zr 49%, Ti 24%, Fe 15%, Nb 9% and S 3%. The preparation and characterization steps of the alloy plate in this embodiment refer to Example 1 and are not repeated here. Figure 1 As shown, the alloy Zr provided by the present invention 49 Ti 24 Fe 15 The material properties and sensitivity of the elastomer prepared by Nb9S3 are shown in Table 1.
[0083] from Figure 1 It can be seen that the X-ray diffraction pattern of the elastomer prepared in Example 1-9 does not have an obvious diffraction peak, but shows a broad scattering peak, which can be used as an indication that the elastomer prepared in Example 1-9 is amorphous.
[0084] Comparative Example 1
[0085] This comparative example illustrates the alloy Zr provided by the present invention. 30 Ti 27 Fe 18 Nb 15 Preparation method of Cr7, that is, the alloy material is composed of the following elements in atomic percentage: Zr 30%, Ti 27%, Fe 18%, Nb 15% and Cr 7%. The preparation and characterization steps of the alloy plate in this comparative example refer to Example 1 and are not repeated here. Figure 2 As shown, the alloy Zr provided by the present invention 30 Ti 27 Fe 18 Nb 15 The material properties and sensitivity of the elastomer prepared by Cr7 are shown in Table 1.
[0086] The alloy Zr provided in this comparative example 30 Ti 27 Fe 18 Nb 15 The yield strength of the elastomer prepared by Cr7 is 1100 MPa and the Young's modulus is 210 GPa. Figure 2 As shown in the figure, through X-ray diffraction (XRD) analysis, it was observed that the alloy elastomer showed obvious crystallization, which may lead to limited forming ability. Crystallization may cause a large number of defects such as crystal planes and phase changes inside the material. In order to evaluate the sensitivity of the alloy elastomer, a calibration test was carried out. In the test, a linear torque was applied to the elastomer, and its sensitivity was measured to be 3.36 mV / (V*N∙m).
[0087] Comparative Example 2
[0088] This comparative example illustrates the alloy Zr provided by the present invention.27 Ti 25 Fe 14 Nb 14 Al 20 The preparation method is as follows, that is, the alloy material is composed of the following elements in atomic percentage: Zr 27%, Ti 25%, Fe 14%, Nb 14%, Al 20%. The preparation and characterization steps of the alloy plate in this comparative example refer to Example 1 and are not repeated here. Figure 2 As shown, the alloy Zr provided by the present invention 27 Ti 25 Fe 14 Nb 14 Al 20 The properties and sensitivity of the prepared elastomer material are shown in Table 1.
[0089] The alloy Zr provided in this comparative example 27 Ti 25 Fe 14 Nb 14 Al 20 The yield strength of the prepared elastomer is 900 MPa and the Young's modulus is 240 GPa. Figure 2 As shown in Figure 2, similarly, through X-ray diffraction (XRD) analysis, it was observed that the alloy elastomer showed obvious crystallization, which may limit its forming ability. Crystallization may cause a large number of defects such as crystal planes and phase changes inside the material. In order to evaluate the sensitivity of the alloy elastomer, a calibration test was carried out. In the test, a linear torque was applied to the elastomer, and its sensitivity was measured to be 2.94 mV / (V*N∙m).
[0090] Comparative Example 3
[0091] This comparative example illustrates the alloy Zr provided by the present invention. 46 Ti 29 The preparation method of Fe8Nb8B9, that is, the alloy material is composed of the following elements in atomic proportion: Zr 46%, Ti 29%, Fe 8%, Nb 8%, B 9%. The preparation and characterization steps of the alloy plate in this comparative example refer to Example 1 and are not repeated here. Figure 2 As shown, the alloy Zr provided by the present invention 46 Ti 29 The properties and sensitivity of the elastomer material prepared by Fe8Nb8B9 are shown in Table 1.
[0092] The alloy Zr provided in this comparative example 46 Ti 29 The yield strength of the elastomer prepared from Fe8Nb8B9 is 1000 MPa and the Young's modulus is 210 GPa. Figure 2As shown, the same defects as those in Comparative Examples 1 and 2 are also found, which will not be repeated here. In order to evaluate the sensitivity of the alloy elastomer, a calibration test was performed. In the test, a linear torque was applied to the elastomer, and its sensitivity was measured to be 3.27 mV / (V*N∙m).
[0093] Comparative Example 4
[0094] This comparative example illustrates the alloy Zr provided by the present invention. 37 Ti 21 Fe 19 7S 16 The preparation method is as follows, that is, the alloy material is composed of the following elements in atomic percentage: Zr 37%, Ti 21%, Fe 19%, Nb 7%, S 16%. The preparation and characterization steps of the alloy plate in this comparative example refer to Example 1 and are not repeated here. Figure 2 As shown, the alloy Zr provided by the present invention 37 Ti 21 Fe 19 7S 16 The properties and sensitivity of the prepared elastomer material are shown in Table 1.
[0095] The alloy Zr provided in this comparative example 37 Ti 21 Fe 19 7S 16 The yield strength of the prepared elastomer is 940 MPa and the Young's modulus is 230 GPa. Figure 2 As shown, the same defects as the above comparative example are also found, which will not be repeated here. In order to evaluate the sensitivity of the alloy elastomer, a calibration test was carried out. In the test, a linear torque was applied to the elastomer, and its sensitivity was measured to be 3.06 mV / (V*N∙m).
[0096] Comparative Example 5
[0097] This comparative example uses a commercial elastomer material (17-4PH stainless steel) to prepare an elastomer, and compares its performance with the elastomer prepared by the present invention. 17-4PH stainless steel is a precipitation hardening stainless steel with good corrosion resistance, high strength and hardness, and excellent mechanical properties. The yield strength of 17-4PH stainless steel is 1200 MPa, the Young's modulus is 220Gpa, and the sensitivity is 2.203 mV / (V*N∙m).
[0098] It can be seen from Table 1 that the alloy material provided by the embodiment of the present invention has a chemical formula of Zr a Ti b Fe c Nb d M e, wherein M is one of Cr, Al, B or S, and a, b, c, d and e satisfy the following conditions: 40≤a≤55, 12≤b≤27, 6≤c≤20, 3≤d≤20, and 0≤e≤6. Wherein, a, b, c, d and e are the atomic ratios of each element in the amorphous alloy. The yield strength of the elastomer prepared by the alloy material is much higher than that of the comparative example, the Young's modulus is much lower than that of the comparative example, and the sensitivity is also much higher than that of the comparative example. Even compared with the commercial elastomer material (17-4PH stainless steel) with good corrosion resistance, high strength and hardness, and excellent mechanical properties, the yield strength of the amorphous alloy elastomer prepared by the alloy material provided by the present invention is much higher, the Young's modulus is lower and the sensitivity is much higher, and the torque sensor manufactured by using the amorphous alloy elastomer of the present invention can effectively solve the problem that the traditional sensor is difficult to reconcile between stiffness and sensitivity.
[0099] The torque sensor is manufactured by using an amorphous alloy elastomer prepared from the alloy material provided by the present invention. In some embodiments, the use principle of the torque sensor is as follows: the fixed mounting surface 2 of the sheet-like elastomer 1 and the mechanical arm at the robot joint are connected by bolts to fix the torque sensor. The strain gauges 4 are evenly distributed along the horizontal direction of the fixed mounting surface 2 and installed on the bottom wall of the strain slot 3. The strain gauges 4 are connected by built-in circuits to form a Wheatstone bridge circuit. The bolts connect the loading mounting surface 6 of the sheet-like elastomer 1 and the joint module motor via threaded holes 8. When the excitation voltage is applied, the torque is at X L =0 N∙m load, the output analog signal is denoted as Y L (mV / V). When the motor torque gradually increases until the target torque X H , the torque sensor is deformed. At the same time, the strain gauge 4 is deformed synchronously, and a measurable strain signal is obtained. The analog signal at this time is recorded as Y H (mV / V). Unload the motor torque to 0 N∙m and repeat the above steps three times or more. The linear equation of the torque sensor can be obtained by the following formula (1). They are the upper and lower limit output signal values (mV / V) of the torque sensor under multiple loading cycles.
[0100]
[0101] Refer to the calibration specification (JB / T 12935-2016) and calculate X according to the corresponding formula ij -Y ij The data of the torque sensor can be calculated at X H Performance parameters under the measuring range include sensitivity, linear deviation, repeatability deviation, hysteresis, zero drift and other technical indicators.
[0102] In some specific embodiments, the excitation voltage is 5-12 V, and the torque is L =0 N∙m load, the output analog signal is denoted as Y L (mV / V). When the motor torque gradually increases until the target torque X H =100 N∙m, the torque sensor is deformed. At the same time, the strain gauge 4 is deformed synchronously, and a measurable strain signal is obtained. The analog signal at this time is recorded as Y H (mV / V). Unload the motor torque to 0 N∙m and repeat the above steps 5 times. Refer to the calibration specification (JB / T 12935-2016) and calculate X according to the corresponding formula. ij -Y ij The data can be calculated that the torque sensor is H =100 N∙m range, including sensitivity, linearity deviation, repeatability deviation, hysteresis, zero drift and other technical indicators. The results are shown in Table 2.
[0103] Example 10
[0104] This embodiment uses the elastomer made of the alloy of Example 1 to manufacture the torque sensor of this embodiment. The raw material used for the elastomer of this embodiment has a thickness of 10 mm, and a length and width of 45 mm. Referring to the above-mentioned torque sensor use principle and performance test steps, the torque sensor of this embodiment is H =100 N∙m range, it has a sensitivity of 7.14 mV / (V*N∙m), a repeatability deviation of 0.47%FS, a linearity deviation of 0.61%FS, a hysteresis of 0.88%FS, and a zero drift of 0.1%FS, as shown in Table 2.
[0105] Embodiment 11
[0106] This embodiment uses the elastomer made of the alloy of Example 5 to manufacture the torque sensor of this embodiment. The raw material used for the elastomer of this embodiment has a thickness of 9 mm, and a length and width of 45 mm. Referring to the above-mentioned torque sensor use principle and performance test steps, the torque sensor of this embodiment is tested at X H =400 N∙m range, it has a sensitivity of 7.05 mV / (V*N∙m), a repeatability deviation of 0.49%FS, a linearity deviation of 0.37%FS, a hysteresis of 0.48%FS, and a zero drift of 0.1%FS, as shown in Table 2.
[0107] Example 12
[0108] This embodiment uses the elastomer made of 17-4PH stainless steel in Comparative Example 5 to manufacture the torque sensor of this embodiment. Referring to the above-mentioned torque sensor use principle and performance test steps, the torque sensor of this embodiment is H =50 N∙m range, it has a sensitivity of 3.203 mV / (V*N∙m), a repeatability deviation of 1.28%FS, a linearity deviation of 0.9%FS, a hysteresis of 1.85%FS, and a zero drift of 0.5%FS, as shown in Table 2.
[0109] From the data in Table 2, it can be seen that the amorphous alloy elastomer prepared by the alloy material provided by the present invention has significant advantages in manufacturing torque sensors. Compared with the elastomer prepared by 17-4PH stainless steel, the performance parameters of the torque sensor of the amorphous alloy elastomer show the following characteristics:
[0110] Sensitivity: The sensitivity of the amorphous alloy elastomer has been more than doubled, which means that the torque sensor can capture torque changes more accurately, thereby improving measurement accuracy.
[0111] Range: The range of amorphous alloy elastomers is significantly increased, which enables torque sensors to adapt to a wider range of application scenarios, including those that need to measure larger torques.
[0112] Linearity deviation: Amorphous alloy elastomers have less linearity deviation, which means that the output of the torque sensor has a better linear relationship with the actual torque, thereby improving the accuracy of the measurement.
[0113] Repeatability: Amorphous alloy elastomers have lower repeatability, which means that when the same torque is measured multiple times under the same conditions, the torque sensor output is more consistent, which is critical to ensuring the reliability and repeatability of the sensor.
[0114] Hysteresis: Amorphous alloy elastomers have less hysteresis, which means that the torque sensor responds faster to torque changes and is not affected by historical loading conditions, thereby improving the real-time performance of the measurement.
[0115] Zero drift: The zero drift of amorphous alloy elastomers is smaller, which means that the torque sensor has better stability under no-load conditions, which is very important for maintaining long-term stability and reliability of measurements.
[0116] Table 1 shows the material properties and sensitivity properties of the amorphous alloy elastomers of Examples 1 to 9 of the present invention and Comparative Examples 1 to 5.
[0117] Table 1
[0118]
[0119] Table 2 shows the torque sensor performance of Example 10, Example 11 and Example 12 of the present invention.
[0120] Table 2
[0121]
[0122] In some embodiments, the Young's modulus of the amorphous alloy elastomer provided by the present invention is 90 GPa-114 GPa; the yield strength of the amorphous alloy elastomer is 1700 MPa-2400 MPa; and the sensitivity of the amorphous alloy elastomer is 6.18 mV / N m-7.34 mV / N m.
[0123] like Figure 3-5 FIG. 1 is a schematic diagram showing the structure of a torque sensor according to an embodiment of the present invention. The torque sensor is a torque sensor having a chemical formula of Zr a Ti b Fe c Nb d M e , wherein M is one of Cr, Al, B or S, and a, b, c, d and e satisfy the following conditions: 40≤a≤55, 12≤b≤27, 6≤c≤20, 3≤d≤20, and 0≤e≤6. Specifically, the amorphous alloy elastomer 1 selects the alloy material of the embodiment and its corresponding atomic proportion. The torque sensor includes an amorphous alloy elastomer and a strain gauge 4, the amorphous alloy elastomer is a circular sheet elastomer 1, the sheet elastomer 1 includes a fixed mounting surface 2, and the upper and lower sides of the fixed mounting surface 2 are provided with strain grooves 3 with side walls and bottom walls, each strain groove 3 is connected through a through groove, and the through groove includes a first groove 9 extending along the radial direction of the sheet elastomer 1 arranged on both sides of the strain groove 3 and a second groove 5 extending along the circumferential direction of the sheet elastomer 1 that penetrates and connects two adjacent first grooves 9, the width of the through groove is 0.8-1.0mm, and the strain gauge 4 is arranged on the bottom wall of the strain groove 3.
[0124] Specifically, the second groove 5 connects the adjacent first groove 9 to form an annular or partially annular structure, and the first groove 9 is evenly arranged along the direction of the circular sheet elastomer 1, thereby achieving connectivity between the through groove and the strain groove 3. In some embodiments, the width of the through groove is 0.8-1.0 mm. The narrower through groove can reduce stress concentration and avoid structural damage caused by excessive local stress. When the torque sensor is subjected to bending moment, the through groove can isolate most of the bending moment, significantly reducing the interference of the bending moment on the torque measurement accuracy of the torque sensor. In addition, the torque sensor proposed in the present invention has a compact structure and enhances the stiffness and use range of the sheet elastomer 1. When the torque sensor is loaded with torque, the strain groove 3 located on the fixed mounting surface 2 can produce a large and uniform elastic strain, thereby improving the sensitivity of the torque sensor and the stability of the measurement signal.
[0125] In some embodiments, the sheet-like elastic body 1 includes a loading and mounting surface 6, and the second grooves 5 are evenly arranged along the circumference of the loading and mounting surface 6, and the through grooves are arranged to release stress and arrange circuits.
[0126] In some embodiments, Figure 4 As shown in the figure, the sheet-like elastic body 1 is in the shape of a stepped flange, and is provided with a fixed mounting surface 2, a loading mounting surface 6 and a centering structure 7 in order of increasing thickness. The centering structure 7 is designed in the shape of a stepped boss and is arranged on the loading mounting surface 6 to achieve precise centering. The centering structure 7 can ensure that the torque sensor and the mechanical arm are precisely docked. Therefore, the above structure not only ensures the matching accuracy of the torque sensor and the mechanical arm, but also can effectively avoid torque eccentricity.
[0127] In some embodiments, the strain grooves 3 are evenly distributed in the horizontal direction of the fixed mounting surface 2, the width of the strain grooves 3 is greater than the width of the through grooves, and the widths of the first grooves 9 and the second grooves 5 are the same. The wider strain grooves 3 can better withstand external loads, reduce the risk of damage caused by local stress concentration, and also help improve the accuracy of measurement.
[0128] In some embodiments, the fixed installation surface 2, the loading installation surface 6 and the centering structure 7 are arranged on different horizontal planes with decreasing diameters in sequence, which not only simplifies the assembly process of the torque sensor, but also avoids the influence of the pre-tightening force of the bolts on the measurement accuracy of the torque sensor during the installation process.
[0129] In some embodiments, the strain gauges 4 are evenly distributed along the horizontal direction of the fixed installation surface 2. The strain gauges 4 are used to obtain measurable strain signals and convert them into analog signals.
[0130] In some embodiments, the strain gauge 4 is preferably a resistance strain gauge.
[0131] In some embodiments, the type of strain gauge 4 is selected from one or more of the following: strain gauge, T-type strain gauge, V-type strain gauge, double-bridge strain gauge, three-grid strain gauge, full-bridge strain gauge. Preferably, the strain gauge 4 is a V-type strain gauge, which has good anti-bending moment crosstalk capability and can provide higher measurement sensitivity and accuracy.
[0132] In some embodiments, strain gauges 4 are provided on the bottom wall of each strain slot 3, and each strain gauge 4 is connected by a signal line to form a Wheatstone bridge circuit. This not only improves the accuracy of the measurement, but also enhances the stability of the signal. Through the balance of the Wheatstone bridge, reliable torque measurement results can be obtained under various working conditions. In addition, this design also allows each strain gauge 4 to be calibrated individually, further improving the measurement accuracy and flexibility of the torque sensor.
[0133] In some embodiments, the strain gauge 4 may be fixed on the surface of the sheet-like elastic body 1 . Preferably, the strain gauge 4 is fixed on the bottom wall of the strain groove 3 of the sheet-like elastic body 1 .
[0134] In some embodiments, a plurality of threaded holes 8 are provided on the fixed mounting surface 2 and the loading mounting surface 6, and the threaded holes 8 are evenly distributed in the horizontal direction of the centering structure 7 and staggered with the strain grooves 3. Preferably, the number of threaded holes on the fixed mounting surface 2 and the loading mounting surface 6 is 6 to 12.
[0135] In some specific embodiments, six threaded holes 8 are evenly arranged on the fixed installation surface 2 to ensure the connection strength between the sheet-like elastic body 1 and the robot arm.
[0136] In some specific embodiments, six strain grooves 3 are evenly arranged on the upper and lower sides of the fixed installation surface 2, and their positions are staggered with the threaded holes 8. In this way, the staggered arrangement can disperse stress, reduce the local stress level, and maintain the overall strength and stability of the fixed installation surface 2.
[0137] In some specific embodiments, six threaded holes 8 are evenly arranged on the loading and mounting surface 6 for bolting the sheet elastic body 1 to the robot joint. This can better withstand and disperse the force and torque generated by the movement of the robot joint, allowing the articulated robot to perform precise motion control in different directions, thereby improving the flexibility and adaptability of the robot.
[0138] In some embodiments, the through groove is processed by milling or water jet machining, which effectively avoids the change of material properties caused by high temperature during wire cutting.
[0139] In some embodiments, the torque sensor has a measuring range of 50 to 400 (N∙m), which can not only meet the needs of most application scenarios, but also maintain a high measurement accuracy, so that the torque sensor can maintain a stable output signal during the measurement process, reduce errors and drifts, and thus improve the accuracy of the measurement.
[0140] In some embodiments, the sensitivity of the torque sensor is not less than 3.0% mV / (V*N∙m). Specifically, the torque sensor is very sensitive to changes in torque and can capture tiny changes in torque.
[0141] In some embodiments, the torque sensor has a repeatability of 0.01% FS to 0.5% FS, a linear error of 0.01% FS to 1% FS, and a hysteresis of 0.01% FS to 0.5% FS. Specifically, the torque sensor can maintain consistent output during multiple measurements and in different directions, thereby improving measurement accuracy and stability.
[0142] In some embodiments, the zero drift of the torque sensor is 0.01% FS to 0.3% FS. Specifically, a small zero drift means that the torque sensor can maintain a stable output during long-term use or environmental changes, further improving reliability.
[0143] In some embodiments, the thickness of the sheet-like elastic body 1 is 0.01 mm to 10.0 mm, preferably 1.0 mm to 10.0 mm, and more preferably 5.0 mm to 7.0 mm.
[0144] In some embodiments, the sensitivity of the amorphous alloy elastomer is 1.0 mV / (N·m) to 10.0 mV / (N·m), preferably 4.0 mV / (N·m) to 6.0 mV / (N·m), and most preferably 5.0 mV / (N·m).
[0145] In some embodiments, the articulated robot includes a torque sensor. Specifically, when the torque sensor is assembled and used with the robot, the torque sensor can detect torque changes caused by external loads or internal power during the movement of the robot joints. When the robot moves quickly or is impacted, the torque sensor can also quickly respond to sudden changes in torque to achieve effective force control and ensure safe operation of the robot when it is impacted or accidentally overloaded.
[0146] Although the present invention has been described through the embodiments, the present invention is not limited to the embodiments described herein, but includes various changes and modifications that may be made without departing from the scope of the present invention.
Claims
1. An amorphous alloy elastomer, characterized in that: The chemical formula of the amorphous alloy is Zr a Ti b Fe c Nb d M e , wherein M is one element selected from Cr, Al, B or S, and a, b, c, d and e satisfy the following conditions: 40≤a≤55, 12≤b≤27, 6≤c≤20, 3≤d≤20, and 0≤e≤6.
2. The amorphous alloy elastomer according to claim 1, characterized in that: The atomic ratio d of Nb satisfies the following condition: 6≤d≤12.
3. The amorphous alloy elastomer according to claim 1, characterized in that: When M is Cr, the value of e is 0<e≤5.
4. The amorphous alloy elastomer according to claim 1, characterized in that: When M is Al, the value of e is 0<e≤6.
5. The amorphous alloy elastomer according to claim 1, characterized in that: When M is B, the value of e is 0<e≤5.
6. The amorphous alloy elastomer according to claim 3, characterized in that: When M is S, the value of e is 0<e≤3.
7. The amorphous alloy elastomer according to any one of claims 1 to 6, characterized in that: The Young's modulus of the amorphous alloy elastomer is 90 GPa-114 GPa; the yield strength of the amorphous alloy elastomer is 1700 MPa-2400 MPa; and the sensitivity of the amorphous alloy elastomer is 6.18 mV / N m-7.34 mV / N m.
8. A torque sensor, comprising the amorphous alloy elastomer and a strain gauge according to any one of claims 1 to 6, characterized in that: The amorphous alloy elastomer is a circular sheet elastomer, which includes a fixed mounting surface, and strain grooves with side walls and bottom walls are arranged on the upper and lower sides of the fixed mounting surface. Each of the strain grooves is connected through a through groove, and the through groove includes a first groove extending along the radial direction of the sheet elastomer and arranged on both sides of the strain groove, and a second groove extending along the circumferential direction of the sheet elastomer and connecting two adjacent first grooves. The width of the through groove is 0.8-1.0mm, and the strain gauge is arranged on the bottom wall of the strain groove.
9. The torque sensor according to claim 8, characterized in that: The sheet-like elastic body comprises a loading and mounting surface, the second groove is arranged along the circumference of the loading and mounting surface, and the through groove is arranged for relieving stress and arranging lines.
10. The torque sensor according to claim 8, characterized in that: The sheet-like elastic body is in a stepped flange shape, and is provided with the fixed installation surface, the loading installation surface and the centering structure in sequence in the order of increasing thickness.